Faktor Penentu Kelelahan Mata Pada Pekerja Pengguna Laptop Di Claim PT X - Sitepu, Meri Ani; Ramadhani, Nur Rizky (Universitas Esa Unggul, 2024)
The average use of laptops among workers in the Claim Department is at least 8 hours per day. Eye fatigue often occurs due to intensive laptop use, which can reduce productivity. This study aims to identify and analyze the relationships between age, gender, length of service, duration of laptop use, and viewing distance to the monitor screen related to eye fatigue among workers in the Claim Department of PT. X in 2024. The approach used in this research is Cross Sectional, with a total population of 60 individuals and sampling conducted through total sampling. The instruments used include questionnaires and measuring tools. Data analysis was performed using the chi-square test, as well as univariate and bivariate analyses. The analysis results showed that 53% of laptop users experienced eye fatigue. There are significant relationships between age (P-value 0.023), duration of laptop use (P-value 0.001), and viewing distance to the screen (P-value 0.001). The duration of laptop use variable shows the highest prevalence ratio (PR) of 15.889, meaning that duration of use increases the risk of eye fatigue by 16 times. To prevent and reduce complaints of eye fatigue, it is recommended that the company install UV radiation filters, adjust proper viewing distances, implement the 20-20-20 method, and conduct regular eye examinations for workers. The purpose of this research is to provide recommendations that can enhance workers' eye health and reduce the risk of eye fatigue due to prolonged laptop use.